Bone mineral density, kidney function and participant‐reported outcome measures in women who switch from tenofovir disoproxil emtricitabine and a nonnucleoside reverse transcriptase inhibitor to abacavir, lamivudine and dolutegravir. Issue 4 (5th December 2021) - Campbell, Lucy; Ibrahim, Fowzia; Barbini, Birgit; Samarawickrama, Amanda; Orkin, Chloe; Fox, Julie; Waters, Laura; Gilleece, Yvonne; Tariq, Shema; Post, Frank A.; ,
Abstract: Objectives: Tenofovir disoproxil fumarate (TDF) is associated with reduced bone mineral density (BMD). The aim of the study was to evaluate changes in BMD in women who switched from TDF, emtricitabine and a nonnucleoside reverse transcriptase inhibitor (TDF/FTC/NNRTI) to abacavir, lamivudine and dolutegravir (ABC/3TC/DTG). Methods: We conducted a randomized controlled trial in which women aged ≥ 40 years were randomized 1:2 to continue TDF/FTC/NNRTI or switch to ABC/3TC/DTG. We analysed changes in BMD at the hip and lumbar spine from baseline to week 96 using linear regression, and markers of bone turnover and kidney function using repeated measures mixed effects models with multiple imputation for missing data. We conducted exploratory analyses of weight, mental health, sleep and symptoms attributed to HIV infection and antiretroviral therapy. Results: Ninety‐one women [mean (standard deviation) age 50.4 (6.6) years] were randomized. Women who switched to ABC/3TC/DTG maintained viral suppression and experienced improvements in BMD at the lumbar spine (but not the neck of the femur or the total hip), bone resorption markers and proteinuria (total protein, albumin and retinol‐binding protein) and modest weight gain without changes in body mass index. Although mean anxiety, depression and sleep scores did not differ between the two study arms, anxiety, depression and sleep disturbance at baseline predicted ABC/3TC/DTG discontinuation for neuropsychiatric side effects [odds ratios (95% confidence intervals) 11.9 (2.0–71.6), 16.0 (2.6–97.9) and 10.0 (1.8–56.0), respectively]. Conclusions: Switching from TDF/FTC/NNRTI to ABC/3TC/DTG improved the BMD of the lumbar spine and kidney function. These benefits need to be balanced against modest weight gain and the need for antiretroviral therapy substitutions in a proportion of participants.